(3JgPjH TQM GdSHY GdeYdbGJ hEYQGHgGs - (3Ydj Hf YHO Gddg GdhgQGfjs ((3GdbGgQI s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg JYGdi Ydi fYeGFg hTcQg Ydi LRjd YWGFg aEfg deG GWdYJ Ydi GdSHY GdeYdbGJ heGJVefJ ef Mce GdYQH heGajgG ef dWGFa GdCOH CMHHJ Cf CPcQgG TQMG Jdhajg Jdh CHj LYaQ QMeg Gddg s
(3BNQgG (B:s
(3fSei GdXGdejf heG XdefG hdcfG SfHOC XGdejfG CdG dG jLYdgf CMO YdjfG afLgd ahb Lgd GdLGgdjfG s
(3GdMHQ HGgJ ai HYV GdehGVYs
(3hHChdgG bUI GeQF GdbjSs
(3hJQJjH GaVdjI GdCTYGQ HYV GdTYQGAs
(3cJH ahb GdYfhGf GdCUdi YfhGf BNQ HNW eMOK TQM GdeYdbGJ GdSHY s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
Keywords: (3GdCOHs